ANALISIS HUKUM EKONOMI SYARIAH TERHADAP PRAKTIK JUAL BELI PADA PRODUK BAI’ AL-WAFA’ DI BMT UGT SIDOGIRI CABANG BULAK RUKEM SURABAYA - setiawan, priyo; wahab, abd (Universitas Muhammadiyah Surabaya, 2019)
AbstrakIslam is a religion that loves brotherhood. Islam teaches good cooperation between humans in the fields of muamalah and transactions. One form of transaction in trading is buying and selling. A person who will build a house will surely he will plan in advance before building his house, either by saving first or collecting building materials needed little by little. There are those who are looking for alternatives in building permanent houses, that is by buying building materials in stages, the buyer will store the building materials that he has bought at a building store. Buyers and shopkeepers enter into a custody agreement. The problem that then arises is if the store uses the stored goods to be sold again to other buyers, even though the store is able to bear the risks that may arise. These problems will be linked in the application of the principle of wadi'ah to the MUI DSN fatwa number 02 / DSN-MUI / IV / 2000 on building materials safekeeping services.This research is analytical descriptive by describing the conditions found in the field and analyzing them to get conclusions. With empirical legal research, the author examines the implementation of the wadi'ah contract on safekeeping of building materials associated with the MUI Fatwa DSN. Descriptive qualitative analysis is used to analyze the reality of the implementation of the wadi'ah contract on safekeeping building materials.The practice of storing building materials in Sumber Urip Surabaya's building stores has fulfilled the terms and conditions of the yaddhamanah wadi'ah contract, where the buyer acts as the entrusted person, while the building store acts as the person who receives the item deposited. The deposit is in the form of cement. It is said yaddhamanah because the building store uses cement from the buyer's savings by selling the cement to other buyers without notifying the buyer when the contract occurs. Keywords: Implementation, Wadi’ah, Safekeeping